Reconstruction of Knee Defects Using Pedicled Gastrocnemius Muscle Flap with Split-Thickness Skin Grafting: A Single Surgeon's Experience with 21 Patients - Kilic, Ali; Denney, Brad; de la Torre, Jorge (The Journal of Knee Surgery, 2019)
Generally, reconstruction of knee defects with exposed bone, joint, tendon, and/or hardware requires a vascularized muscle flap for coverage. Although there are several surgical options for a knee defect reconstruction, the pedicled gastrocnemius muscle still remains the workhorse flap. Although this flap is commonly used for knee defect reconstruction and the technique is described very well, there is an absence of information in the literature detailing the technique of harvesting and insetting of the gastrocnemius flap step by step with illustrations. The purpose of this article is to describe in detail the technique to reconstruct defects of the knee with pedicled gastrocnemius muscle flap as well as to present demographics and surgical results of 21 patients who had knee reconstruction with a pedicled gastrocnemius muscle flap and split-thickness skin grafting.
Keywords: gastrocnemius flap; knee defects; periprosthetic infection